2015
DOI: 10.1111/tid.12345
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for pre‐ and post‐engraftment bloodstream infections after allogeneic hematopoietic stem cell transplantation

Abstract: Risk factors for BSI in the pre-engraftment period were the interval between diagnosis and transplantation (261 days or more), engraftment failure, and high-risk disease status at HSCT in a multivariate analysis. No significant risk factor for BSI in the post-engraftment period was identified by a univariate analysis. These findings may be useful for deciding upon empiric antibacterial treatment for HSCT recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
56
3
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 18 publications
8
56
3
5
Order By: Relevance
“…Kikuchi et al 20 showed similar results in their retrospective review, noting that BSIs were more common in the pre-(39% of patients) vs post-engraftment (17% of patients) periods. During the pre-engraftment period, important risk factors for BSI are neutropenia, presence of a CVC and severe mucositis.…”
Section: Epidemiologysupporting
confidence: 59%
See 3 more Smart Citations
“…Kikuchi et al 20 showed similar results in their retrospective review, noting that BSIs were more common in the pre-(39% of patients) vs post-engraftment (17% of patients) periods. During the pre-engraftment period, important risk factors for BSI are neutropenia, presence of a CVC and severe mucositis.…”
Section: Epidemiologysupporting
confidence: 59%
“…21 In multivariate analysis, pre-engraftment BSI has been associated with engraftment failure and high-risk disease status at the time of HCT. 20 Post-engraftment BSIs are more commonly found in patients who undergo allo-HCT and have a history of acute (aGvHD) or chronic GvHD (cGvHD). Patients with post-engraftment BSI received more antibacterial prophylaxis, previous antibiotic therapy and immunosuppression (corticosteroids and cyclosporine) than patients without BSI.…”
Section: Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations
“…11,14,16,19,27,29,35,36,39 Haematological malignancies represented the main cause of neutropenia; seven studies included also patients with solid cancer (ranging from 5% to 44% of the patient population). Acute leukaemia was the most common haematological disease in 17 (57%) studies.…”
Section: 39mentioning
confidence: 99%